THE IMPACT OF SOCIAL MEDIA ADDICTION ON ADOLESCENTS MENTAL HEALTH - nurhandini wulandari (Yayasan Pendidikan Medika Indonesia, 2025)
The use of social media in Indonesia continues to rise rapidly, with 139 million active users in 2024, reflecting a significant impact on the lives of adolescents. Along with the increase in digital activity, the prevalence of mental health disorders among teenagers has also shown a concerning trend, with anxiety disorders and major depression being the most common. This study aims to examine the influence of social media addiction on adolescent mental health through a literature review approach. Based on the findings of the literature review, it was discovered that excessive duration of social media use is associated with increased symptoms of anxiety disorders, depression, sleep disturbances, and a decline in self-image. Furthermore, adolescents who spend more than three hours per day on social media are at high risk of experiencing psychological disorders that may disrupt their quality of life. This study also discusses the importance of intervention efforts, such as limiting social media access time, strengthening emotional regulation, and support from family and the surrounding environment to mitigate these negative impacts. A balance between social media use and mental health needs to be maintained in order to promote psychological well-being among adolescents.